Enhanced Understanding of the Levels of Palliative Care in Pharmacy Students Through Participating in Clinical Training in Hospitals. (June 2017) - Myotoku, Michiaki; Omotani, Sachiko; Hatsuda, Yasutoshi; Konishi, Hiroki; Hirotani, Yoshihiko
Objective: A palliative care knowledge survey was conducted involving pharmacy students to examine their perceived usefulness and the educational effect of clinical training in hospitals. Methods: A questionnaire sheet was distributed to fifth-year pharmacy students before and after clinical training. The questionnaire consisted of questions to clarify the details of palliative care-related training in hospitals and students' knowledge of such care. The respondents were divided into 2 groups: those who participated in palliative care team (PCT) rounds (group A: 57) and those who did not (group B: 57). Results: The mean total correct answer rate markedly increased after training in group A, from 37.9 to 47.1% (P < .01). Such an increase was also observed in the domains of philosophy and pain in this group ( P < .01). In contrast, group B did not show differences in the mean correct answer rate between before and after training; there was no significant increase in the rate in any domain. Conclusion: Pharmacy students' knowledge was enhanced by participating in the PCT, confirming the usefulness of such participation during training as part of palliative care education.